Uncovering True Participant Needs in SMEs Training to Enhance Training Service Quality - Ghanif Faoziansyah; Yati Rohayati; Muhammad Iqbal (International Journal of Innovation in Enterprise System, 2024)
It is recognized in various countries that Small and Medium-Sized Enterprises have played anessential role in the nation's economic development. However, despite the large number of Small andMedium-Sized Enterprises, only a few have succeeded in developing their businesses and movingupmarket. Various efforts from various parties, both government and private, have been made to helpbuild the competencies needed to develop Small and Medium-Sized Enterprises businesses. One waythis has been done is through training, such as that conducted by Rumah BUMN Bandung. However,the data shows that the movement provided has yet to have a significant positive impact on thedevelopment of Small and Medium-Sized Enterprises businesses. Therefore, a study was conductedto identify the needs of Small and Medium-Sized Enterprises for effective training by applying theKano Model and Training Service Quality. Data was collected by surveying Small and Medium-SizedEnterprises who attended training at Rumah BUMN Bandung. Of the 130 respondents whoparticipated in the assessment of 15 attributes of needs, it was found that there are 11 needs referredto as "True Participant Needs" that are currently not fulfilled. Among these needs, ten attributesrequire improvement, while the remaining require further development. These findings are expectedto overcome the gap in fulfilling Small and Medium-Sized Enterprise's needs related to effectivetraining